PERHITUNGAN SALDO KAS OPTIMUM PADA BANK XYZ DENGAN MENGGUNAKAN METODE BOUMUL DAN MILLER ORR - , Fajar Anugerah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cash management in Banking Industry require special intention cause by it related with liquidity risk, operational risk and profitability risk of a bank, therefore effective cash management is a mandatory Objective of this study is to calculate optimum cash balance in Bank XYZ using Miller Orr methodelogy Result shows Bank XYZ using most of its net cash flow (70%) to mitigate future liquidity risk in form of current account at Bank Indonesia. Optimum cash balance counted using Miller Orr Methodlogy is IDR 1,117,390,084,183 lower compared than targeted optimum cash balace by Bank XYZ management which is IDR.1.5 Trilliun